Generation Z Adoption of QRIS in Semarang City : Role of Financial Risk Tolerance - Rachma, Annisa Luthfiyah; Kusuma, Pradana Jati (Neo Journal of economy and social humanities, 2024)
This study explores Generation Z's adoption of QRIS in Semarang City using the UTAUT framework. It examines how performance expectancy, effort expectancy, social influence, and facilitating conditions impact financial risk tolerance and intentions to use of digital payment QRIS. According to Bank Indonesia, QRIS has seen significant growth, with 50.50 million users in 2024 and a 226.54% increase in transactions compared to the previous year. Data from 165 respondents aged 18–27, analyzed with SEM-PLS, revealed that all UTAUT variables positively influence financial risk tolerance, which in turn impacts QRIS adoption. Performance expectancy had the strongest effect, while facilitating conditions showed minimal impact, indicating the need for infrastructure improvements. Recommendations include enhancing security, upgrading infrastructure, and educating users to promote QRIS as a reliable digital payment tool in Indonesia.